THE ANALYSIS OF FIGURATIVE LANGUAGE IN “GIRL ON FIRE” SONG LYRICS BY ALICIA KEYS - Indra Sopiansyah; Ratih Inayah (PROJECT (Professional Journal of English Education), 2021)
Figurative languages are languages that use figures of speech, not literal meanings. This research analyzed the figurative language used in the lyric of Girl on Fire by Alicia Keys. The purpose of this research is to find out the types of figurative language in the lyrics of the song Girl on Fire by Alicia Keys and to analyze the contextual meaning of figurative language used in that song lyrics. It is hoped that the results of this study will be useful for readers, especially in describing what figurative language and what kind of figurative language are. The method of this research is descriptive qualitative research. The lyrics of song is got from (Keys, 2012) entitle Girl on Fire. The result found that there are some kinds of figurative language used in Alicia Keys’ song entitle Girl on Fire, such as alliteration, cliché, hyperbole, idiom, imagery, metaphor, personification, repetition, similie, and symbol. The contextual meaning of each figurative language is also clarified. The conclusion of this research is there are some kinds of figurative language use by Alicia Keys in her song titled Girl on Fire.